التنبؤ بالتعثر المالي لبعض المؤسسات العاملة في القطاع الخاص الصناعي بولاية غرداية باستخدام التحليل التمييزي خلال الفترة) 2009-2014 - بن سانية, عبد الرحمان; بن شاعة, وليد (University of Eloued جامعة الوادي, 2017)
يهدف هذا المقال إلى دراسة التنبؤ بالتعثر المالي لبعض المؤسسات الصناعية بولاية غرداية للفترة الممتدة من (2009-2014)، وذلك باستخدام أسلوب التحليل التمييزي بهدف الإجابة عن إشكالية هذه الورقة البحثية التي تتمحور حول قدرة المؤشرات المالية على التنبؤ بتعثر المؤسسات الصناعية. تضمنت الدراسة حالة ثلاث مؤسسات منها مؤسستين متعثرتين وواحدة سليمة لمحاولة بناء نموذج قياسي للتنبؤ بالتعثر، وقد تبين من خلال هذه الدراسة أن هناك أربعة مؤشرات مالية من بين ثمانية المؤشرات المستخدمة لها القدرة على التمييز وهي:الأصول المتداولة إلى الخصوم المتداولة، الإيرادات إلى مجموع الأصول، الإيرادات إلى صافي رأس المال، الأموال الخاصة إلى الأصول غير الجارية،في حين توصلت الدراسة إلى أن احتمالية تمييز الوضعية المالية من خلال القراءة التحليلية للنسب المالية ضعيفة، وهذا ما يفسر قصور النسب المالية لوحدها في التنبؤ بالتعثر المالي للمؤسسات الصناعية، كما أثبت النموذج المتوصل إليه جودة تصنيف عالية جدا حيث بلغت نسبة 100% والتي يمكن من خلالها التمييز بدقة بين المؤسسات الصناعية. Abstract: This article aims at studying prediction of the financial falter for some industrial foundations in the state of Ghardaia for the period between 2009 to 2014, by using a discriminatory analysis method .In order to answer the problematic of this paper, which focuses on the ability of the financial indicators to predict the falter of the industrial foundations. The study included three industrial foundations, two faltering of foundations and one of them was healthy, that by trying to create a standard model for predicting the falter. The study showed that there are four out of eight financial indicators used in the study that have the ability to distinguish: Assets transferred to current liabilities, revenue to total assets, revenue to net capital, special fundus to noncurrent assets, while the study concluded that probability of discrimination the financial position through analytical reading of ratios was weak as the qualification quality of the model was very high 100%, through which it is possible to distinguish accurately between industrial foundations
Prediction of the financial falter for somefoundationsoperating in the private industrial in the state of Ghardaiaby using discriminatory analysis during the period (2009-2014)
مجلة رؤى المجلد السابع العدد 12
Keywords: تنبؤ، تعثر مالي،مؤسسات صناعية، تحليل تمييزي، مؤشرات مالية; prediction , Financial falter, industrial foundations, Discriminat Analysis, Financial indicators. (JEL) Classification : O40 ,E24, C10.